UPGRADING MENTAL HEALT MELALUI KEBIJAKAN KEPEMIMPINAN KEPALA SEKOLAH: PERSPEKTIF KURIKULUM YANG ADAPTIF - Rois Mahmudi; Muhammad Ilmi Najib; Ainur Rofiq (DEVELOPMENT: Journal of Community Engagement, 2025)
This study aims to analyze how principal policies can improve students' mental health through the implementation of an adaptive curriculum. This study uses a qualitative approach with a case study type. Case studies are chosen because this method allows researchers to explore phenomena in depth related to the implementation of an adaptive curriculum. The location of the study was at Madrasah Aliyah Al Amiriyyah Blokagung Banyuwangi, the largest private school in the Banyuwangi area. Data in this study were collected through interviews, observations and documentation. Data were analyzed using the Miles and Huberman interactive model, which includes data reduction, data presentation and drawing conclusions. The validity of the data was tested through triangulation of sources and techniques. The results of the study indicate that upgrading mental health through principal leadership oriented towards an adaptive curriculum is a strategic step in forming a generation of learners who are emotionally and academically resilient. This study contributes to providing a conceptual and practical basis for the development of integrative school policies between principal leadership and adaptive curriculum in order to improve students' mental health sustainably. Keywords: Mental Health; Principal Policy; Adaptive Curriculum.